Antimicrobial capacity of Aloe vera and propolis dentifrice against Streptococcus mutans strains in toothbrushes: an in vitro study - Patrícia Fernanda Roesler Bertolini; Oswaldo Biondi Filho; Arnaldo Pomilio; Sérgio Luiz Pinheiro; Meghi Silva de Carvalho (Journal of Applied Oral Science, 2012)
OBJECTIVES: This study evaluated in vitro the efficiency of Aloe vera and propolis dentifrice on reducing the contamination of toothbrush bristles by a standard strain of Streptococcus mutans (ATCC 25175; SM), after toothbrushing. MATERIAL AND METHODS: Fifteen sterile toothbrushes were randomly divided into 5 toothbrushing groups: I (negative control): without dentifrice; II: with fluoridated dentifrice; III: with triclosan and gantrez dentifrice; IV (positive control): without dentifrice and irrigation with 10 mL of 0.12% chlorhexidine gluconate; V: with Aloe vera and propolis dentifrice. In each group, 1 sterile bovine tooth was brushed for 1 min, where the toothbrush bristles were contaminated with 25 µL of SM. After toothbrushing, the bristles were stored in individual test tubes with 3 mL of BHI under anaerobiosis of 37°C for 48 h. Then, they were seeded with sterile swab in triplicate in the Mitis salivarius - Bacitracin culture medium. The samples were kept under anaerobiosis of 37°C for 48 h. Scores were used to count the number of colony forming units (cfu). The results were submitted to the Mann-Whitney statistical test at 5% significance level. RESULTS: There was statistically significant difference (p<0.05) for the reduction of bristle contamination comparing groups II, III, IV and V to group I. CONCLUSIONS: It may be stated that after toothbrushing, the Aloe vera and propolis dentifrice reduced the contamination of toothbrush bristles by SM, without differentiation from the other chemical agents used.